Sinergy of extra-terrestrial particle accelerators and accelerators operated in the terrestrial atmosphere. Issue 1 (1st December 2022) - Chilingarian, A; Hovsepyan, G; Zazyan, M
Abstract: We performed simulations of the EAS particle transport initiated by ultra-high-energy gamma rays entering the terrestrial atmosphere. During thunderstorms, the electric fields above the LHAASO array efficiently modulate EAS particles. Because of this modulation, the possible bias on the energy estimation for primary energies up to 100 TeV can be up to ten-fold. Moreover, for the higher primary energies (≈1 PeV), the electric field modulation enlarges "genuine" primary gamma ray energy 2.5-3 times. This result is very important because observation of PEVatrons by LHAASO is based on rather small statistics, and the highest energy events can occasionally coincide with thunderstorms. We also demonstrate the existence of a threshold effect on the intracloud E-field strength needed to trigger the startup of a runaway process that exponentially multiplies the free electrons entering a strong atmospheric electric field.